1992
DOI: 10.1109/23.211373
|View full text |Cite
|
Sign up to set email alerts
|

Single event upset rates in space

Abstract: SEUs in the CRRES MEP showed a dramatic increase during a solar flare, the influence of the flare varied widely among device types, and a GaAs RAM showed a different response to the proton belts than some Si RAMS. Corrections to the SEU rate to account for orbital dwell time emphasize the dramatic difference between the rate in the proton belts and the rate due to cosmic ray ions above the belts. In the case of one device, apparent total dose damage resulted in a large increase in upsets due to unreliable devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…They can result from external disturbances like power supply instability in industrial applications or as cosmic radiations in space applications [1]. Some recent studies claim that transient and intermittent faults are becoming also a problem in general purpose groundbased systems.…”
Section: Introductionmentioning
confidence: 99%
“…They can result from external disturbances like power supply instability in industrial applications or as cosmic radiations in space applications [1]. Some recent studies claim that transient and intermittent faults are becoming also a problem in general purpose groundbased systems.…”
Section: Introductionmentioning
confidence: 99%
“…For systems that operate in harsh environments, the fault arrival rate can be as high as 10 -2 to10 2 per hour [13]. For example, in an orbiting satellite, the number of errors caused by protons and cosmic ray ions was measured to be as high as 35 in a 15-minute interval [13].…”
Section: Fault Arrival Ratementioning
confidence: 99%
“…For example, in an orbiting satellite, the number of errors caused by protons and cosmic ray ions was measured to be as high as 35 in a 15-minute interval [13].…”
Section: Fault Arrival Ratementioning
confidence: 99%
“…Similar failure rate for permanent faults is also considered in where the fault rate of a computer node for heavy duty trucks is derived based on the MIL-HDBK-217 standard. Experiments by Campbell et al (1992) using an orbiting satellite containing a microelectronics test system found that, within a small time interval (∼15 min), the number of errors due to transient faults could be quite high. Since non-permanent faults are more frequent, the failure rate of random non-permanent hardware faults in each core during non-bursty period is λ r = 10 −4 /h.…”
Section: Parameters Of Fault Modelmentioning
confidence: 99%